RISK ANALYSIS OF TENDER PRICE INCREASE USING ANALYTICAL HIERARCHY PROCESS (AHP) (CASE STUDY : PT INTI PRIMA TEKNIK) (The Indonesian Journal of Business Administration, 2021)
With the more advanced science and technology today, competition in the business world shows a rapid increase. This competition requires companies to have a strategy to win the competition, one of which is by winning the project auction. In a project auction, the cost aspect is one of the primary considerations in the construction project implementation process because it involves a large amount and is susceptible to risk. The beginning of cost control is from the estimation process. Inaccurate cost estimates will have a negative impact on the entire construction process. Because the estimate is a reference in preparing a budget and is used as a control for project costs, an analysis of the dominant risk is needed to be used as a basis for mitigation.PT Inti Prima Teknik is a company engaged in manufacturing spare parts and services, especially in the form of metal and rubber. The projects undertaken by PT IPT come from state-owned companies located in West Sumatra. To get the project, a tender auction is required with several competitors. In the continuation of the tender auction, PT IPT had to experience several defeats because its value was small compared to other companies. This study aims to determine the risks that cause a price increase in the tender offer to cause defeat.By using qualitative methods, it is hoped that this research can provide benefits to the organization. This study's primary data came from interviews with company leaders and several high-ranking officials who were directly involved in the formulation of tender prices. Secondary data were collected from company documents related to the tender auction. Then the data will be processed using the Analytical Hierarchy Process (AHP.) Method.The results of the AHP found that five candidates were the causes of the tender defeat. Later, it can be used as an additional parameter in formulating the price at the next tender auction.Keywords: Analytical Hierarchy Process, AHP, Service Business, Decision Making, Risk Management